Clinical and Functional Characterization of a Missense ELF2 Variant in a CANVAS Family - Ahmad, Hena; Requena, Teresa; Frejo, Lidia; Cobo, Marien; Gallego-Martinez, Alvaro; Martin, Francisco; Lopez-Escamez, Jose A.; Bronstein, Adolfo M. (Frontiers in Genetics, 2018)
Cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS) is a rare disorder with an unknown etiology. We present a British family with presumed autosomal dominant CANVAS with incomplete penetrance and variable expressivity. Exome sequencing identified a rare missense variant in the ELF2 gene at chr4:g.140058846 C > T, c.10G > A, p.A4T which segregated in all affected patients. By using transduced BE (2)-M17 cells, we found that the mutated ELF2 (mt-ELF2) gene increased ATXN2 and reduced ELOVL5 gene expression, the causal genes of type 2 and type 38 spinocerebellar ataxias. Both, western blot and confocal microscopy confirmed an increase of ataxin-2 in BE(2)-M17 cells transduced with lentivirus expressing mt-ELF2 (CEE-mt-ELF2), which was not observed in cells transduced with lentivirus expressing wt-ELF2 (CEE-wt-ELF2). Moreover, we observed a significant decrease in the number and size of lipid droplets in the CEE-mt-ELF2-transduced BE (2)-M17 cells, but not in the CEE-wt-ELF2-transduced BE (2)-M17. Furthermore, changes in the expression of ELOVL5 could be related with the reduction of lipid droplets in BE (2)-M17 cells. This work supports that ELF2 gene regulates the expression of ATXN2 and ELOVL5 genes, and defines new molecular links in the pathophysiology of cerebellar ataxias.